Pengaruh Lingkungan Kerja dan Motivasi Terhadap Kinerja Karyawan Melalui Kreativitas Karyawan Pada Distrik I PT. Perkebunan Nusantara III - Akbar, Helmi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to analyze the Effect of Work Environment and Motivation on Employee Performance through Employee Creativity in District I PTPN III. To answer this problem we conducted research on 242 employees. The method used is quantitative research looking at Multiple Linear Regression analysis with the formula Z = α + β1x1 + β2x2 + Y. The data used are primary data through filling out questionnaires and secondary data through documentation studies. The results showed that the variables of Work Environment and Motivation simultaneously had a positive and significant effect on Employee Creativity. Work Environment and Creativity variables simultaneously have a positive and significant effect on Employee Performance. While Motivation and Creativity have a positive and significant effect on Employee Performance in Serdang I District PT. Nusantara Plantations III.